Petrographic and geochemichal characters of the Bitlis ignimbirite - Kiliç, Ayşe Didem; Çakmak, Büşra (Gumushane University, 2021)
In this study were investigated mineralogical and geochemical properties and phase relations of Bitlis ignimbrites being product of Nemrut volcanism. The Bitlis ignimbirite have different colors and composition ratios. Its mineralogical composition is a pyroclastic rock sequence consisting of plagioclase, sanidine, anorthoclase, augite, olivine, biotite, hematite, quartz and ilmenite. The Bitlis ignimbrite is formed as a result of eruption of magma in trachyh-riolite composition formed in volcanic arcs, back-arc or intra-continental areas or contamination of magma during rising in intra-continental fracture. There are differences in component ratio, chemical composition and color between ignimbrite levels. This unit showed pre-caldera period and shows mainly pumice, rock fragments, oriented fiammes, features such as sepiolytic particles together with conversion to sanidine mineral indicate at least two phases and the devitrication partially causes color difference. Mineral alterations and high Ba/Sr (1.48-1.92), Ba/Ta (33.0-34.6), Th/La (0.24-0.25), Ba/La (11.2-15) ratios indicates metamorphism or crustal contamination post or during formation of ignimbrite. The geochemical features of the Bitlis ignimbrite partly show a small volume silicic volcanism. The discrepancy between three levels may be due to time interval between phase stages and magmatic processes or from the devitrification. © 2021, Gumushane University. All rights reserved.
Bitlis ignimbiritinin petrografik ve jeokimyasal özellikleri
Keywords: Anortoclase; Devitrification; Fe-Ti oxides; Ignimbirite; The Nemrut; Trace element geochemistry